The influence of regional original income, allocated funds on capital expenditure in Padang Sidempuan city - Muhammar Syafii; Muhammad Fitri Ramadhana; Fitrawaty Fitrawaty (Institute of Computer Science (IOCS), 2023)
Government areas in the planning budget area need to provide attention to the enhancement of Income Regional Originals (PAD) and Allocation Funds General (DAU), as research results show that both are influential, significant and direct to Growth Economics. Enhancement quality Source Power Humans (HR) can increase PAD and DAU. Therefore, the region's government must improve education and training for inhabitant areas. Use of Allocation Funds Special (DAK) must be evaluated repeatedly because the research results show that DAK has no direct effect on Growth Economics. Focus on improving the Growth Economy through the effort of government areas in strengthening sectors that have the potential to enhance Growth Economics, like sector tourism, industry, agriculture, and trade. Although PAD, DAU and DAK do not directly affect Capital Expenditures, the Growth Economy directly influences Capital Expenditures. Therefore, the government should focus on Growth Economics in planning capital expenditure to strengthen sectors that can improve Growth Economics. Research can identify other influencing factors to the region's Growth Economy and Capital Expenditures so that the government can formulate more policies to strengthen Growth Economics and Capital Expenditures.